Design and Analysis of a Wide Stopband Microstrip Dual-band Bandpass Filter - Yahya, Salah I.; Rezaei, Abbas; Khaleel, Yazen A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
A novel configuration of a dual-band bandpass filter (BPF) working as a harmonic attenuator is introduced and fabricated. The proposed filter operates at 3 GHz, for UHF and SHF applications, and 6.3 GHz, for wireless applications. The presented layout has a symmetric structure, which consists of coupled resonators. The designing of the proposed resonator is performed by introducing a new LC equivalent model of coupled lines. To verify the LC model of the coupled lines, the lumped elements are calculated. The introduced filter has a wide stopband up to 85 GHz with 28th harmonic suppression, for the first channel, and 13th harmonic suppression, for the second channel. The harmonics are attenuated using a novel structure. Also, the proposed BPF has a compact size of 0.056 λg2. Having several transmission zeros (TZs) that improve the performance of the presented BPF is another feature. The proposed dual-band BPF is fabricated and measured to verify the design method, where the measurement results confirm the simulations.